Prosecution of Traffic Violators According to Law Number 22 Year 2009 - Moch. Mufied Al'an; M. Hidayat (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
The 1945 Constitution of the Republic of Indonesia has mandated in article 1 paragraph (3) that our country is a state of law, so let it be law as its commander, especially in an era of democracy that craves law as its main pillar. The purpose of this study is to provide action to traffic offenders. The research method used is normative juridical law research, which is research based on literature study which includes primary legal materials, secondary legal materials and tertiary legal materials. The results of the research on the value of our legal awareness penetrate into the conscience and become the needs of every individual, of course in order to anticipate the low value of legal awareness, the government through institutions in charge of law must proactively improve the legal education system for citizens (department of justice through the Pos Komalu program, state police). Republic of Indonesia through awareness programs for security and public order and others), it is hoped that the value of legal awareness of citizens will increase so that they know and understand that if there are legal problems that befall them, they can exercise their rights before the law, especially regarding the issue of Law no. 22 of 2009 concerning road traffic and transportation.